Theoretical study of the CIDNP kinetics of the reaction of a photo-excited dye with a reactive spot on the surface of a sphere: application to CIDNP of proteins - Ivanov, K; Yurkovskaya, A; Hore, P; Lukzen, N (2006)
Time-resolved chemically induced dynamic nuclear polarization (CIDNP) in sterically specific photoreactions of proteins with excited dye molecules is studied theoretically by means of the integral encounter theory. The protein is modeled as a chemically inert sphere with one small reactive spot, with steric factor f modeling a single accessible CIDNP-active amino acid residue on its surface. Kinetic equations describing the dye-quenching kinetics and the CIDNP time evolution are obtained, and the non-trivial f dependence of the rate constant of dye quenching, the geminate CIDNP intensity, the radical recombination rate constant and the nuclear T 1 relaxation time are studied. Protein CIDNP kinetics are compared with those of free amino acids.